Experimental evidence of phase transition of silica polymorphs in basaltic eucrites: implications for thermal history of protoplanetary crust - Rei Kanemaru; Naoya Imae; Akira Yamaguchi; Aiko Nakato; Junko Isa; Makoto Kimura; Hirotsugu Nishido; Tomohiro Usui; Takashi Mikouchi (Scientific Reports, 2024)
Abstract Silica polymorphs occur under various pressures and temperature conditions, and their characteristics can be used to better understand the complex metamorphic history of planetary materials. Here, we conducted isothermal heating experiments of silica polymorphs in basaltic eucrites to assess their formation and stability. We revealed that each silica polymorph exhibits different metamorphic responses: (1) Quartz recrystallizes into cristobalite when heated at ≥ 1040 °C. (2) Monoclinic (MC) tridymite recrystallizes into no other polymorphs when heated at ≤ 1070 °C. (3) Silica glass recrystallizes into quartz when heated at 900–1010 °C, and recrystallize into cristobalite when heated at ≥ 1040 °C. These results suggest that MC tridymite in eucrites does not recrystallize into other polymorphs during the reheating events, nor does it recrystallize from other silica phases below the solidus temperature of eucrite (~ 1060 °C). Additionally, we found that pseudo-orthorhombic (PO) tridymite crystallizes from quenched melts in the samples heated at ≥ 1070 °C. Previously, cristobalite has been considered as the initial silica phase, which crystallizes from eucritic magma. Our findings suggest that the first crystallizing silica minerals may not always be cristobalite. These require a reconsideration of the formation process of silica minerals in eucrites.